Pengaruh Lifestyle Terhadap Keputusan Pembelian Smartphone OPPO di Kota Bima - Juhal Hidayat; Sri Ernawati; Juwani Juwani (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of lifestyle on purchasing decisions of OPPO smartphones in Bima City. The research employed a quantitative approach with a causal associative research design. The population consisted of consumers who had purchased and used OPPO smartphones in Bima City, while the sample comprised 50 respondents selected using purposive sampling. Data were collected through observation, questionnaires, and literature review, and analyzed using validity and reliability tests, simple linear regression, correlation coefficient, coefficient of determination, and t-test with the assistance of SPSS 22. The results indicate that lifestyle has a positive and significant effect on purchasing decisions of OPPO smartphones in Bima City. This is evidenced by a regression coefficient of 0.454, a t-value of 2.404, which is greater than the t-table value of 2.011, and a significance value of 0.020 (<0.05). The correlation coefficient of 0.328 indicates a low level of relationship, while the coefficient of determination (R²) of 0.107 shows that lifestyle explains 10.7% of the variance in purchasing decisions, with the remaining 89.3% influenced by other factors not examined in this study. Therefore, lifestyle is one of the factors influencing consumers' purchasing decisions of OPPO smartphones in Bima City.